The beer directory : an international guide - Wood, Heather (Storey Communications, 1995)
The Beer Directory includes : Breweries, Brewpubs, organizations, places to enjoy beer, Places to buy beer, Festivals, Books, Magazines & Beer People, Songs, Anecdotes, Museums, recipes, plus cider makers & importers.